The Obsessive-Compulsive Symptoms in Tic Disorders and the Psychometric Properties of Children's Yale-Brown Obsessive-Compulsive Scale: An Evidence-Based Survey in a Chinese Sample - Junjuan Yan; Yi Gu; Mengyu Wang; Yonghua Cui; Ying Li (Frontiers Media S.A., 2022)
ObjectivePatients with tic disorders (TDs) usually also have obsessive-compulsive disorder (OCD). The severity of obsessive-compulsive symptoms (OCSs) in TD is widely evaluated using the Children's Yale-Brown Obsessive-Compulsive Scale (CY-BOCS). However, there is no survey on the severity of OCSs in patients with TD based on a Chinese sample, and the reliability and validity of the CY-BOCS in patients with TD have not been well established in China. This study examined the severity of OCSs in TDs and the psychometric properties of the CY-BOCS in Chinese pediatric patients with TD.MethodsA total of 367 patients who were diagnosed with TD [152 with Tourette syndrome (TS)] were enrolled in the Department of Psychiatry at Beijing Children's Hospital in China. The mean age of the patients was 9.21 ± 2.06 years (range: 5-16 years). The Yale Global Tic Severity Scale (YGTSS) and CY-BOCS were used as screening tools. The psychometric properties of the CY-BOCS were assessed using Cronbach's alpha, test-retest reliability, and construct validity.ResultsThe OCSs in TDs were 3.93 ± 5.15 based on the CY-BOCS in the whole sample. The older adolescent group showed higher scores than the young adolescent groups (Z = −3.37, p = 0.001). However, the young adolescent group showed a higher incidence rate of OCSs than the older adolescent group (p < 0.01). Men with TDs also showed a higher incidence rate of OCSs than women (p = 0.03). The reliability and validity analyses of the CY-BOCS showed Cronbach's alpha and test-retest reliability values of 0.81 and 0.82, respectively. The CY-BOCS showed an acceptable level in the two-factor structure (obsession and compulsive) in patients with TD. The comparative fit index (CFI) was 0.84 for TD, 0.86 for Tourette, 0.94 for the younger adolescent group, and 0.74 for the older adolescent group.ConclusionMore OCSs were identified in the TS group and the older adolescent group with TDs. The CY-BOCS showed good psychometric properties in children and adolescents with TD, especially in younger patients with TD. OCSs might be associated with age and functional impairment of TD.